2015
DOI: 10.1016/j.sjbs.2014.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of halophilic cellulase production from locally isolated fungal strain

Abstract: Halophilic cellulases from the newly isolated fungus, Aspergillus terreus UniMAP AA-6 were found to be useful for in situ saccharification of ionic liquids treated lignocelluloses. Efforts have been taken to improve the enzyme production through statistical optimization approach namely Plackett-Burman design and the Face Centered Central Composite Design (FCCCD). Plackett-Burman experimental design was used to screen the medium components and process conditions. It was found that carboxymethylcellulose (CMC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 18 publications
(16 reference statements)
0
12
1
Order By: Relevance
“…In particular, some of the enzyme activities are higher than those of previous studies elsewhere. For example, cellulase activity (6Á92 IU g À1 ) in our study was higher than the studies of Gunny et al (2015) with an activity of 0Á0625 U ml À1 and Kalsoom et al (2019) with the activity of 0Á158 U ml À1 . In addition, higher a-Lrhamnosidase activity (5Á83 IU g À1 ) was obtained in the present work compared to the results obtained in the SSF of Aspergillus terreus in wheat bran (1Á11 U ml À1 ) and bagasse of sugarcane (1Á70 U ml À1 ) described by Elinbaum et al (2002).…”
Section: Fungal Growth Metabolism and Enzyme Productioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In particular, some of the enzyme activities are higher than those of previous studies elsewhere. For example, cellulase activity (6Á92 IU g À1 ) in our study was higher than the studies of Gunny et al (2015) with an activity of 0Á0625 U ml À1 and Kalsoom et al (2019) with the activity of 0Á158 U ml À1 . In addition, higher a-Lrhamnosidase activity (5Á83 IU g À1 ) was obtained in the present work compared to the results obtained in the SSF of Aspergillus terreus in wheat bran (1Á11 U ml À1 ) and bagasse of sugarcane (1Á70 U ml À1 ) described by Elinbaum et al (2002).…”
Section: Fungal Growth Metabolism and Enzyme Productioncontrasting
confidence: 80%
“…For example, cellulase activity (6·92 IU g −1 ) in our study was higher than the studies of Gunny et al . () with an activity of 0·0625 U ml −1 and Kalsoom et al . () with the activity of 0·158 U ml −1 .…”
Section: Resultsmentioning
confidence: 87%
“…The highest FPase activity of A. terreus UniMAP AA-6 was 0.0625 U mL À1 in the presence of 7.70% NaCl (w/v). 58 The crude enzyme of P. oxalicum HC6 in this work was determined under different NaCl solution (0-15.0%, w/v) at 60 C with initial pH 5.0 for 1 h. Every enzyme activity (FPase, CMCase and b-glucosidase) was considered as 100% at NaCl concentration of 0%. As shown in Fig.…”
Section: Stability Of Enzyme Activity Of P Oxalicum Hc6 Under Nacl Amentioning
confidence: 99%
“…Surprisingly, the hydrolytic enzymes were produced optimally when 2.5% inoculum size was used with cellulase activity of 1024.22 U/mg and xylanase activity of 779.82 U/mg while 2% inoculum size supported the production of the oxidative enzymes with specific activities of 415.45 U/mg and 757.41 U/mg for laccase and peroxidase, respectively ( Figure 4 ). Presence of abundant spores in inoculum has been reported to facilitate rapid proliferation and biomass synthesis for enzyme production as was evident with the production of cellulase and xylanase obtained in this study [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 60%
“…Reports have shown that lower inoculum sizes favour the production of these enzymes as it was reported that the nutrient and oxygen levels in the fermentation media are sufficient for the growth of fungi and therefore enhanced production of lignocellulolytic enzymes [ 36 ]. Gunny et al [ 33 ] reported maximum cellulase production from Aspergillus terreus with 4% inoculum. Omojasola et al in their study reported a decline in glucose production by some fungi when cultured on pineapple waste at inoculum sizes above 6% and 8% using A. niger and above 4% and 6% for fermentations using T. longibrachiatum as a result of low yield of cellulase [ 37 ].…”
Section: Resultsmentioning
confidence: 99%